Dampak Pembangunan Jalan Tol Terhadap Perkembangan UMKM Di Kabupaten Serdang Bedagai - Habib Aulia Akbar; Supriadi .; Mila Naeruz (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
The construction of toll roads has various impacts on Micro, Small, and Medium Enterprises (MSMEs). On the one hand, it improves market access, distribution efficiency, business opportunities, and employment opportunities. On the other hand, toll road development changes community mobility patterns, resulting in reduced traffic flow along existing routes. Consequently, some MSMEs experience a decline in the number of customers, sales turnover, and business activities. The research problem addressed in this study is whether toll road construction has an effect on the sales turnover, number of employees, and number of customers of MSMEs. This study aims to analyze the impact of toll road construction on the performance of Micro, Small, and Medium Enterprises (MSMEs), as measured by sales turnover, the number of employees, and the number of customers. This study employed a quantitative research approach. Data were collected through questionnaires distributed to MSME owners in areas affected by toll road construction. The data were analyzed using statistical analysis techniques to examine the effect of toll road construction on the research variables. The results of the study indicate that toll road construction has a significant effect on the sales turnover, number of customers, and number of employees of Micro, Small, and Medium Enterprises (MSMEs). These findings demonstrate that toll road development brings substantial changes to the economic activities of MSMEs, creating both opportunities for business expansion and challenges arising from shifts in consumer traffic. Therefore, appropriate policies are needed to maximize the benefits of infrastructure development while minimizing its negative impacts on MSMEs through empowerment programs, improved market access, enhanced competitiveness, and continuous support from the government and other stakeholders. Such efforts will ensure that infrastructure development is carried out in parallel with the strengthening of the MSME sector as one of the key pillars of regional and national economic development.